Implementasi Model Project Based Learning (PjBL) dalam Pembelajaran Sintaksis Bahasa Indonesia - Akhyaruddin Akhyaruddin; Hilman Yusra (Universitas Batanghari Jambi, 2023)
This research was conducted in the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education (FKIP) of Jambi University, in the odd semester of 2021/2022. This study aims to build an authentic, collaborative, and participatory learning climate in an effort to improve student learning achievement in understanding Indonesian Syntax learning materials through project-based learning-case method (PjBL) learning innovation. The method used is the Research and Development (R&D) method, in which the research data is in the form of a PjBL learning plandesign and its implementation is observed and assessed by colleagues using the PjBL learning plan aand implementation instrument in Indonesia Syintax learning. The results show that PjBL planning is very good with a score of 3,7 and the implementation of PjBL in Indonesia Syintax learning is very good with a score of 3,0. The results also show that learning activities of Indonesia Syintax based on PjBL can create an authentic, collaborative and participatory learning atmosphere in solving real problems/cases of Indonesia Syintax to achieve the course learning objectives with an average value of student learning outcomes, learning group I = 95 (A), learning group II = 97 (A), learning group III = 94 (A), learning group IV = 91 (A), and learning group V = 97 (A).